Faktor yang Mempengaruhi Penggunaan ChatGPT Terhadap Penulisan Tesis dalam Kalangan Pelajar Pasca Siswazah di UTHM - Mohamad Aliff Aiman Mohd Zawawi; Anim Zalina Azizan (Research in Management of Technology and Business, 2024)
The development of AI Technology such as ChatGPT greatly helps post-graduate students in the process of preparing a thesis in terms of faster information gathering and the use of more structured vocabulary. The purpose of this study is to measure two main objectives, namely to identify the factors that influence the use of ChatGPT for thesis writing among postgraduate students at UTHM. The second objective is to study the dominant factors that influence the use of ChatGPT on thesis writing among postgraduate students at UTHM. This study focuses on post-graduate students at the Master’s and Doctorate levels at Universiti Tun Hussein Onn Malaysia (UTHM) who are currently preparing to write a thesis or dissertation. Quantitative methods were used to obtain information. The data obtained was analyzed using the Statistical Package for Social Science (SPSS) version 27 to obtain strong results. The results of the study found that among the factors that influence the use of ChatGPT are digital transformation era 4.0, knowledge, transparency and ethics as well as the challenge of writing a thesis. The results of the study found that the digital transformation factor of era 4.0 is the dominant factor that affects the use of ChatGPT for thesis writing. The limitations faced by researchers are in terms of time constraints and the limited data and information collection process. However, a suggestion that researchers can make in the future is to expand the study population to all levels of study and lecturers.